Rhythmic Bdnf and TrkB expression patterns in the prefrontal cortex are lost in aged rats - Coria Lucero, Cinthia Daiana (2016)
Aging brain undergoes several changes leading to a decline in cognitive functions. Memory and learning-related genes such as Creb, Bdnf and its receptor TrkB, are expressed in different brain regions including prefrontal cortex. Those genes’ proteins regulate a wide range of functions such as synaptic plasticity and long-term potentiation. In this work, our objectives were: 1) to investigate whether Creb1, Bdnf and TrkB genes display endogenous circadian expression rhythms, in the prefrontal cortex of rats maintained under constant darkness conditions; 2) to study the synchronization of those temporal patterns to the local cellular clock and 3) to evaluate the aging consequences on both cognition-related genes and activating clock transcription factor, BMAL1, rhythms. A bioinformatics analysis revealed clock-responsive (E-box) sites in regulatory regions of Creb1, Bdnf and TrkB genes. Additionally, cAMP response elements (CRE) were found in Bdnf and TrkB promoters. We observed those key cognition-related factors expression oscillates in the rat prefrontal cortex. Creb1 and TrkB mRNAs display a circadian rhythm with their highest levels occurring at the second half of the 24 h period. Interestingly, the cosinor analysis revealed a 12-h rhythm of Bdnf transcript levels, with peaks occurring at the second half of the subjective day and night, respectively. As expected, the BMAL1 rhythm's acrophase precedes Creb1 and first Bdnf expression peaks. Noteworthy, Creb1, Bdnf and TrkB expression rhythms are lost in the prefrontal cortex of aged rats, probably, as consequence of the loss of BMAL1 protein circadian rhythm and altered function of the local cellular clock.